Perspektif Mahasiswa Akuntansi Pada Diamond Fraud Theory - Friska Cahya Wulandari; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The purpose of this study is to analyze and know the perspective of accounting students about Diamond Fraud theory in the prevention of Fraud. The data collection technique used in this research is to conduct interviews. The analytical technique used is descriptive analysis with a qualitative approach. The results of this study indicate that the three students from different universities said that the Diamond Fraud Theory is very helpful in preventing the occurrence of fraud and for accounting students it is very necessary to study this in order to become professional accountants and with integrity.